CHALLENGES TO PARTICIPATORY DEVELOPMENT IN A RURAL CROSS-BORDER AREA OF THE WESTERN BALKANS - Geertrui, Louwagie; Fabien, Santini; Gert, Guri; Marius, Lazdinis; Ilić, Boban; Paloma Sergio, Gomezy (Economics of Agriculture, 2013)
The World Bank, the Canadian International Development Agency (CIDA), USAID and the International Relief/Development Project (IRDP) concluded in different reports that participatory development programs are invariably more effective at addressing local needs and interventions are more often sustained given the engagement of local actors. The main objective of this paper is to present a detailed appraisal of the implementation process of a well-known participatory approach (the UNDP-designed Area-Based Development - ABD) in the challenging context of a rural, cross-border area (in the Western Balkans). Besides reviewing the theoretical and empirical advantages of participatory and endogenous development, this case study reflects the practical shortcomings related to the selection process of a target area and to obtaining commitment from different agents in a post-conflict zone. This article also highlights that adequate implementation of participatory practices is crucial to obtain accurate quantitative and qualitative data (to guide the development agenda) and secure the involvement of both local and (inter)national actors. The latter is an important factor in fostering long-term engagement to development strategies and the achievement of results that are relevant for the local community and in harmony with national policies and international agreements.